(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Compensation of IOP does not always lead to a stabilization of the glaucomatous process. Therefore, functional and morphometric studies to evaluate the effectiveness of glaucoma surgery are important and necessary. Purpose. To evaluate hypotensive effect of endotrabeculoectomy and influence of the operation on stabilization of glaucoma progressing. Material and methods. The investigation was done in two groups. The first group (22 patients, 23 eyes) was with open-angle glaucoma who underwent endotrabeculoectomy, and the second group (95 patients, 107 eyes) had open-angle glaucoma and cataract who underwent combined phacoemulsification and endotrabeculoectomy. Results. In the first group tonometric IOP decreased by 7.8+0.7 mm Hg and was 18.6+1.1 (p<0.05) in 6 months after the operation and in the second group IOP decreased by 5.2±0.6 mm Hg and was 18.9±1.2 mm Hg (p<0.05). In the follow up period IOP remained compensated and stable. Mean light sensitivity in patients with IOP<22 mm Hg decreased by 0.3±0.2 dB per year (p<0.05), and in patients with IOP over 22 mm Hg — by 0.6±0.4 dB per year (p<0.05). Pattern standard deviation in patients with IOP<22 mm Hg increased by 0.1±0.1 dB (p<0.05), and in patients with IOP over 22 mm Hg — by 0.4+0.3 dB (p<0.05) per year. Morphometric indices of the optic nerve disc during two years after the operation didn’t change significantly in the patients of both groups. Conclusion. Endotrabeculoectomy has an evident hypotensive effect. Results of standard automated perimetry, optical coherent tomography of the optic nerve disc, and measurement of thickness of the retinal nerve fiber layer confirmed stabilization of glaucoma progressing after the operation.